Botulinum toxin type A success rates and predictive factors for favourable outcomes in paediatric patients with acquired esotropia - Narisa Rattanalert; Teechaya Nonboonyawat; Supaporn Tengtrisorn; Penny Singha; Orapan Aryasit; Juthamat Witthayaweerasak; Manupol Tangthongkum (PLoS ONE, 2025)
Purpose This study aimed to assess the efficacy of botulinum toxin type A in treating childhood-acquired comitant esotropia and identify predictive factors of treatment success. Methods This retrospective, consecutive, non-comparative cohort study included children under 18 years treated with botulinum toxin type A for acquired comitant esotropia between 2013 and 2019, with a minimum 6-month follow-up. The primary outcome was the success rate of achieving horizontal deviation within 10 prism dioptres at 6 months post-botulinum toxin type A treatment. Results In total, 49 children with a mean treatment age 8.10 ± 4.02 years were assessed. The three most common types of esotropia were acute acquired comitant, intermittent, and cyclic esotropia (57.2%, 20.4%, and 12.2%, respectively). The mean esodeviation at near and distance was 42.55 ± 13.39 and 42.65 ± 13.35 prism dioptres, respectively. The botulinum toxin type A treatment success rate was 51% (25/49), with survival analysis indicating a declining cumulative probability of treatment success over time (48%, 28%, and 21% at 12, 18, and 24 months, respectively). Significant predictive factors for successful outcomes were pre-botulinum toxin type A esodeviation >30–50 prism dioptres (p = 0.008) and time from diagnosis to treatment <2 months (p = 0.001). Conclusion Botulinum toxin type A demonstrated a success rate of 51% at 6 months with pre-botulinum toxin type A esodeviation and early treatment identified as predictive factors for treatment success suggesting its clinical application.